Evaluating indwelling devices and other risk factors for mortality in invasive Carbapenem-resistant Enterobacterales infections in Georgia, 2012-2019 - Lucy S. Witt; Mary Elizabeth Sexton; Gillian Smith; Monica Farley; Jesse T. Jacob (Cambridge University Press, 2023)
Abstract Objective: Carbapenem-resistant Enterobacterales (CRE) infections are a public health threat due to the risk of transmission between patients and high associated mortality. We sought to identify risk factors for mortality in patients with invasive CRE infections and to specifically evaluate whether there was an association between indwelling medical devices and 90-day mortality. Design: Retrospective observational cohort study of patients infected with CRE in the eight-county metropolitan Atlanta area between 2012 and 2019. Methods: Patients with invasive CRE infections were identified via the Georgia Emerging Infections Program's active, population- and laboratory-based surveillance system and linked with the Georgia Vital Statistics database. We used bivariate analysis to identify risk factors for mortality and completed log binomial multivariable regression to estimate risk ratios (RR) for the association between indwelling devices and mortality. Results: In total, 154 invasive CRE infections were identified, with indwelling devices present in most patients (87.7%) around the time of infection. Admission to an intensive care unit was found to be associated with 90-day mortality (adjusted RR [aRR] 1.55, 95% CI 1.07, 2.24); however, the presence of any indwelling device was not associated with increased risk of 90-day mortality in multivariable analysis (aRR 1.22, 95% CI 0.55, 2.73). Having at least two indwelling devices was associated with increased mortality (aRR 1.79, 95% CI 1.05, 3.05). Conclusions: Indwelling devices were prevalent in our cohort but were not consistently associated with an increased risk of mortality. Further studies are needed to examine this relationship and the role of device removal.